Surface Passivation Studies on n+pp+ Bifacial Solar Cell - Suhaila Sepeai; M. Y. Sulaiman; Kamaruzzaman Sopian; Saleem H. Zaidi (International Journal of Photoenergy)
Bifacial solar cell is a specially designed solar cell for the production of electricity from both sides of the solar cell. It is an active field of research to make photovoltaics (PV) more competitive by increasing its efficiency and lowering its costs. We developed an n+pp+ structure for the bifacial solar cell. The fabrication used phosphorus-oxy-trichloride (POCl3) diffusion to form the emitter and Al diffusion using conventional screen printing to produce the back surface field (BSF). The n+pp+ bifacial solar cell was a sandwiched structure of antireflective coatings on both sides, Argentum (Ag) as a front contact and Argentum/Aluminum (Ag/Al) as a back contact. This paper reports the solar cell performance with different surface passivation or antireflecting coatings (ARC). Silicon nitride (SiN) deposited by Plasma-Enhanced Chemical Vapor Deposition (PECVD), thermally grown silicon dioxide (SiO2), PECVD-SiO2, and SiO2/SiN stack were used as ARC. The efficiency obtained for the best bifacial solar cell having SiN as the ARC is 8.32% for front surface illumination and 3.21% for back surface illumination.